1972
DOI: 10.1037/h0033388
|View full text |Cite
|
Sign up to set email alerts
|

Associative responses to double entendre words as a function of repression-sensitization and sexual stimulation.

Abstract: The sexual associations and associative latencies of repressers and sensitizers to double entendre and asexual stimulus words were studied under conditions of sexual arousal and nonarousal. The results indicated (a) that sexual arousal led to an increment in sexual responses primarily for sensitizers, (6) that sensitizers gave more sexual associations than repressers, with the effect being more marked under sexual arousal conditions, and (c) that sexual stimulation produced a decrement in the speed with which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Similarly, the WAT proved to be insufficiently discriminating among the experimental variables. The only near significant finding was the unsurprising effect for double-entendre versus neutral words in which associative responses to the former had longer latencies (Galbraith & Lieberman, 1972).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the WAT proved to be insufficiently discriminating among the experimental variables. The only near significant finding was the unsurprising effect for double-entendre versus neutral words in which associative responses to the former had longer latencies (Galbraith & Lieberman, 1972).…”
Section: Discussionmentioning
confidence: 96%
“…The fact that a substantial part of reactions could unequivocally be assigned to the hypothesized categories underscores the usefulness of the proposed more differentiated assessment of reactions to ambiguous stimuli. Previous research based on the repression–sensitization construct has considered solely the relative balance (e.g., frequency) in the activation of threatening and nonthreatening meaning alternatives of ambiguous stimuli (e.g., Blaylock, 1963; Galbraith & Lieberman, 1972; Haney, 1973). This procedure appears to rest on the implicit assumption that in the majority of cases either one or the other of these two interpretations is actually made.…”
Section: Discussionmentioning
confidence: 99%
“…More encouraging results were reported by Galbraith and Lieberman (1972), who assessed associations to double entendre words with alternative sexual and asexual meanings. The authors found that sensitizers gave more sexual associations than repressers, especially when participants were led to expect the occurrence of stimuli with sexual connotations in advance.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The sensitizer uses the intellectualizing defense of approaching and identifying with overtly threatening material. Similarly to low sex-guilt individuals, sensitizers have been shown to provide more sexual word associations than repressers under neutral conditions (Schill, 1969) and after exposure to an erotic stimulus (Galbraith & Lieberman, 1972). However, these theoretically expected differences have often not been demonstrated for female subjects.…”
mentioning
confidence: 99%